PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Nelmawati, Nelmawati (Jurnal Pendidikan Guru, 2018)
The problem in this research is the low of mathematics learning result of fourth grader of SD Negeri 72 Pekanbaru with average 57,35 with KKM 70. The purpose of this study is to improve the results of learning mathematics class IV SD Negeri 72 Pekanbaru. This study was conducted in three cycles. In the process of thinking pair share learning, students are actively involved in the learning process, students exchange ideas and opinions in solving problems so that students can complete the task on time. The result of the research shows that there is an increase of mathematics learning result of fourth grade students of SD Negeri 72 Pekanbaru after the action is done in the form of learning with cooperative type think pair share (TPS) model. This can be seen from the students daily average score. Students learning outcomes before action are categorized as low on average 57.35, while in daily repeat cycle I 74.44, daily test cycle II with an average of 82.22, and daily repetition of cycle III with an average of 89.20. Percentage of teacher activity in cycle I 70,83%, with good category, cycle II 81,24%, with very good category, and cycle III 91,66%. While the percentage of student activity in cycle I 64,56% with good category, cycle II with percentage 81,24%, with very good category and cycle III 89,58% with very good category. Based on the results of research and analysis of the data, it can be concluded that the implementation of cooperative learning model type Think Pair Share (TPS) can improve student learning outcomes of grade IV SD Negeri 72 Pekanbaru.